Effect of EthanolicExtract of Centella asiatica againts Adrenal Gland CortexCell Lipid Droplet Feature Induced by Chronic Immobilization Stress in Rats - Mochammad Fairuz Zahran; Brian Wasita; Nanang Wiyono; Ratih Puspita Febrinasari (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2015)
Background: Chronic stress can increase the lipid droplet in cortex cell and adrenal gland damage. Pegagan extract contains such as asiaticoside, flavonoids and triterpenoid are known have antioxidant effect. The objective of the present study was to investigate the beneficial effects of Ethanolic Extract of Centella asiatica (EEC) on adrenal gland cortexcell lipid droplet feature induced by immobilization stress in male rats. Method: This study was a laboratory experimental study with randomized post test only control group design. Paraffin blocks from thirty five male rats previously subjected with chronic immobilization stress and then divided into 6 groups: control group given distilled water 1 mg/kg, stress + PGA, stress + 150 mg/kg EEC, stress + 300 mg/kg EEC, stress + 600 mg/kg EEC and stress + fluoxetine 10 mg. The treatments were performed for 21 consecutive days. Lipid droplet was evaluated using Scoring Lipid Content from Hematoxylin Eosin staining. Statistic analysis was performed using Kruskall-Wallis test continued by Post Hoc Mann-Whitney Test with Bonferroni correction. Result: Results of Kruskall Wallis test showed significant differences in six groups with p = 0.000. Mann Whitney test with Bonferroni correction showed a significant difference between control group with stress + PGA and stress + 600 mg/kg EEC. Fluexetine as positive control show the most effective dose in this study (p = 0,000). There were no significant difference between fluoxetine as control positive and control group (p = 0,112). Conclusion: Stress + 600 mg/kg EEC has beneficial effect on preventing adrenal gland cortexcell lipid droplet feature induced by chronic immobilization stress in rat. Keywords : Centella asiatica, chronic immobilization stress, adrenal glands lipid droplet feature